An Empirical Analysis on Labor Unions and Occupational Safety and Health Committees' Activity, and Their Relation to the Changes in Occupational Injury and Illness Rate - Kwan Hyung Yi; Hm Hak Cho; Jiyun Kim (Elsevier, 2011)
Objectives: To find out from an analysis of empirical data the levels of influence, which a labor union (LU) and Occupational Safety and Health Committee (OSHC) have in reducing the occupational injury and illness rate (OIIR) through their accident prevention activities in manufacturing industries with five or more employees. Methods: The empirical data used in this study are the Occupational Safety and Health Tendency survey data, Occupational Accident Compensation data and labor productivity and sales data for the years 2003 to 2007. By matching these three sources of data, a final data set (n = 280) was developed and analyzed using SPSS version 18 (SPSS Inc., Chicago, IL, USA). Results: It was found that a workplace with a LU has a lower OIIR than one without a LU. In manufacturing industries with five or more employees in 2007, the OIIR of the workplaces without a LU was 0.87%, while that of workplaces with a LU was much lower at 0.45%. In addition, workplaces with an established OSHC had a lower OIIR than those without an OSHC. Conclusion: It was found that the OIIR of workplaces with a LU is lower than those without a LU. Moreover, those with the OSHC usually had a lower OIIR than those without. The workplace OIIR may have an impact on management performance because the rate is negatively correlated with labor productivity and sales. In the long run, the OIIR of workplaces will be reduced when workers and employers join forces and recognize that the safety and health activities of the workplace are necessary, not only for securing the health rights of the workers, but also for raising labor productivity.